Speciation and periodic restricted environments. The case of genus Ononis L. (subsections Natrix and Viscosae). (4th May 2019) - Castro, I.; Rocha, J.; Costa, C.; Costa, G.; Ramírez-Rodríguez, R.; Amich, F.; Carnide, V.; Crespí, A. L.
Abstract: The morpho–environmental similarity between subsections Natrix and Viscosae has been pointed out as the reason for the genetic complexity of these groups of taxa. Based on this characterization a question emerges: could a very recent ongoing evolutionary process explain that morpho–environmental similarity? ISSR and cpSSR amplifications for 45 specimens belonging to taxa of Natrix and Viscosae subsections were developed, along their biogeographic distribution areas. Twenty-nine haplotypes were detected in the biogeographic area of both subsections, 79% were exclusive haplotypes, but the rest is shared between subsections Natrix and Viscosae species. Could that haplotype sharing be the result of potential hybridization between these taxa? Do current environmental conditions restrict the gene flow among taxa? The combination of ancestral genetic polymorphism, introgression, coalescence processes and periodic restricted environments (PRE) by glacial–interglacial environmental dynamics were discussed to explain the relevant percentage of exclusive haplotypes detected, as well as the persistence of shared haplotypes. These results are in accordance with the morpho–environmental proximity previously described for both subsections.